EFEKTIVITAS KEBIJAKAN PERENCANAAN BIAYA PENDIDIKAN DALAM MENDUKUNG PENINGKATAN KUALITAS PEMBELAJARAN: SYSTEMATIC LITERATURE REVIEW - Susilo, Hari; Attalikhtia, Wiwit; Windi Setiawan, Ahmad; Harsono; Suyatmini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational cost planning policy is one of the key aspects of supporting effective educational management and improving the quality of learning. Well-planned educational budgeting enables educational institutions to allocate resources efficiently to support teacher professional development, the provision of learning facilities and infrastructure, the integration of educational technology, and the implementation of high-quality teaching and learning processes. However, previous studies have shown that increasing education funding does not always lead to improvements in learning quality, as the implementation of educational cost planning policies continues to face various challenges, including inadequate budget planning, ineffective financial management, and limited supervision of education fund utilization. This study aims to analyze the effectiveness of educational cost planning policies in improving learning quality, identify the factors influencing their implementation, and formulate recommendations to enhance the effectiveness of educational financial planning. The study employed a Systematic Literature Review (SLR) approach by reviewing scientific articles published between 2021 and 2026 from various national and international academic databases. The selected articles were screened based on predetermined inclusion and exclusion criteria and were analyzed using content analysis through data classification, synthesis, and interpretation. The findings indicate that the effectiveness of educational cost planning policies is influenced by several key factors, including needs-based budget planning, school principals' managerial capacity, transparency and accountability in financial management, stakeholder participation, and continuous monitoring and evaluation. Effective educational cost planning contributes to more efficient budget utilization, strengthens teachers' professional development, improves the availability of learning facilities, and enhances both the learning process and learning outcomes. Therefore, educational cost planning policies should be implemented in a systematic, participatory, transparent, and needs-oriented manner to provide optimal support for improving the quality of learning.